Design and experiment of a bionic drag-reducing digger for tuberous crops under heavy soil conditions. - Ranbing Yang; Wenjian Xu; Zhiguo Pan; Huan Zhang; Zhixi Deng (PLoS ONE)
Aiming at the problems of high working resistance and high energy consumption in potato crop harvesting in sticky soil, this paper designs a potato bionic drag-reducing digging shovel based on the streamline shape of catfish head. Based on the theoretical analysis and discrete element method (DEM) simulation, the main factors affecting the digging resistance are the angle of entry, forward speed and vibration frequency, and the digging resistance increases with the increase of forward speed, and decreases with the increase of vibration frequency. Through the orthogonal test in the field, the optimal working parameters of the drag reduction performance are determined with the digging resistance as the test index, and the comparative test of the different shovel shapes is carried out with this parameter. The results show that the optimal solution is to use bionic shovel, with an entry angle of 15°, an operating speed of 0.27m/s, and a vibration frequency of 6Hz. The average digging resistance of the bionic shovel is 3612.86N, and the bionic digging shovel reduces resistance by 17.76% relative to an ordinary flat shovel, and 21.09% relative to the plane triangle shovel. The effect of drag reduction is remarkable, and the structure of the digging shovel bionic is reasonable, which can satisfy the requirements of resistance reduction and consumption reduction of potato harvesting under the conditions of sticky and heavy soils.